Developing techinc of the Enzyme-linked immunosorbent assay in the serodiagnosis of Systemic lupus erythematosus - Mayuna Srisuphanunt (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 1979